Application of Elements of Human Resource Management Strategic: Does it Affect the Work Performance of Koperasi Kencana Makmur Lamongan Employees? - Wahyuningsih, Yulie; Suyitno, Suyitno (Publisher Cv. Inara, 2022)
This study aims to describe efforts to improve work performance through the application of strategic HRM elements and employee performance achievements covering efforts to compl ete tasks, understanding task perceptions, output quality, output quantity, work time effectiveness, and career development at the Koperasi Kencana Makmur. Using descriptive and inferential statistical analysis methods. Descriptive analysis was used to det ermine respondents' perceptions of strategic HRM elements and employee performance. Furthermore, relative frequency analysis, average count and maximum and minimum values of variables, indicators and research items were carried out, to measure the relation ship between variables using multiple linear regression analysis. Aims to explain the influence of strategic HRM elements on work performance. Using the population of all permanent employees of the Koperasi Kencana Makmur. Sampling using proportional strat ified random sampling technique, because the population has elements that are not homogeneous and proportional stratified, with a sample of 60 respondents. The results of this study indicate that there are four independent variables, namely: growth and lea rning of all personnel (X4), integration with company strategy (X5), owning and developing collaboration (X8) and the active role of employees in developing the company's business (X9) which have a significant effect on achievement employee work, while the other five variables namely: employees' understanding of external influences (X1), understanding of labor market dynamics and competition (X2), having a long - term focus (X3), having and developing technical capabilities (X6) and owning and developing conc eptual ability (X7) has no significant effect on employee performance. that the variable active role of employees in developing the company's business has a greater regression coefficient of 0.512 than the regression coefficients of other variables. It can be emphasized that the variable active role of employees in developing the company's business has a dominant and positive influence on employee performance in the Koperasi Kencana Makmur.